INCLUSÕES PLAQUETÁRIAS SEMELHANTES A Anaplasma platys (Ehrlichia platys) EM GATO - VAMILTON ALVARES SANTARÉM (Colloquium Agrariae, 2005)
This article describes a case of a feline, female, aproximatelly eight months of age which had multiple fractures. On hematologic examination were observed normochromic normocytic anemia, and were verified inclusions like-Anaplasma platys (Ehrlichia platys) in platelets. This is the first observation of the rickettsia in cat.